A South African Breast Implant-Associated Anaplastic Large Cell Lymphoma: Clinical Presentation and Six-Year Follow-Up - Alexandra Grubnik; Yastira Ramdas; Barend Van der Bergh; Simon Nayler; Carol-Ann Benn; Bernardo L. Rapoport (Case Reports in Oncological Medicine)
Breast augmentation is the most common surgical procedure for women globally, with 1,795,551 cases performed in 2019. Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is highly uncommon, with 733 reported cases as of January 2020. In South Africa, there are less than 4000 breast augmentation surgeries annually. This case presents the first case report documentation of a South African woman diagnosed with BIA-ALCL. The patient was a 61-year-old woman who consulted the Breast Care Centre of Excellence in Johannesburg in 2015. She had a prior history of bilateral augmentation mammoplasty with subsequent implant exchange. The patient presented with periprosthetic fluid with a mass-like enhancement on the left breast. Aspiration of the mass-like fluid was positive for CD45, CD30, and CD68 and negative for CD20 and ALK-1, indicative of BIA-ALCL. Surgical treatment included bilateral explantation, complete capsulectomies, and bilateral mastopexy. Macroscopic examination of the left breast capsulectomy demonstrated fibrous connective tissue. The histological examination of the tumor showed extensive areas of broad coagulative necrosis with foamy histiocytes. Immunohistochemistry examination of this tumor showed CD3-, CD20-, and ALK-1-negative and CD30- and CD68-positive stains. PCR analysis for T-cell clonality showed monoclonal T-cell expansion. These findings confirm the presence of BIA-ALCL. The patient recovered well after surgery and did not require adjuvant therapy. A patient with a confirmed diagnosis of BIA-ALCL was successfully treated with explantation and complete capsulectomy. She was followed up regularly for six years, and the patient remains well and in remission.